Preliminary evaluation of safety and migration of immune activated mesenchymal stromal cells administered by subconjunctival injection for equine recurrent uveitis - Cassano, Jennifer M.; Leonard, Brian C.; Martins, Bianca C.; Vapniarsky, Natalia; Morgan, Joshua T.; Dow, Steven W.; Wotman, Kathryn L.; Pezzanite, Lynn M. (Frontiers in Veterinary Science, 2023)
Introduction: Equine recurrent uveitis (ERU), an immune mediated disease characterized by repeated episodes of intra-ocular inflammation, affects 25% of horses in the USA and is the most common cause of glaucoma, cataracts, and blindness. Mesenchymal stromal cells (MSCs) have immunomodulatory properties, which are upregulated by preconditioning with toll-like receptor agonists. The objective was to evaluate safety and migration of TLR-3 agonist polyinosinic, polycytidylic acid (pIC)-activated MSCs injected subconjunctivally in healthy horses prior to clinical application in horses with ERU. We hypothesized that activated allogeneic MSCs injected subconjunctivally would not induce ocular or systemic inflammation and would remain in the conjunctiva for >14 days. Methods: Bulbar subconjunctiva of two horses was injected with 10 x 106 pIC-activated (10 μg/mL, 2h) GFP-labeled MSCs from one donor three times at two-week intervals. Vehicle (saline) control was injected in the contralateral conjunctiva. Horses received physical and ophthalmic exams (slit lamp biomicroscopy, rebound tonometry, fundic examination, and semiquantitative preclinical ocular toxicology scoring (SPOTS)) every 1-3 days. Systemic inflammation was assessed via CBC, fibrinogen, and serum amyloid A (SAA). Horses were euthanized 14 days following final injection. Full necropsy and histopathology were performed to examine ocular tissues and 36 systemic organs for MSC presence via IVIS Spectrum. Anti-GFP immunohistochemistry was performed on ocular tissues. Results: No change in physical examinations was noted. Bloodwork revealed fibrinogen 100-300mg/dL (ref 100-400) and SAA 0-25μg/mL (ref 0-20). Ocular effects of the subjconjucntival injection were similar between MSC and control eyes on SPOTS grading system, with conjunctival hypermia, chemosis and ocular discharge noted bilaterally, which improved without intervention within 14d. All other ocular parameters were unaffected throughout the study. Necropsy and histopathology revealed no evidence of systemic inflammation. Ocular histopathology was similar between MSC and control eyes. Fluorescent imaging analysis did not locate MSCs. Immunohistochemistry did not identify intact MSCs in the conjunctiva, but GFP-labeled cellular components were present in conjunctival phagocytic cells. Discussion: Allogeneic pIC-activated conjunctival MSC injections were well tolerated. GFP-labeled tracking identified MSC components phagocytosed by immune cells subconjunctivally. This preliminary safety and tracking information is critical towards advancing immune conditioned cellular therapies to clinical trials in horses.